Late Cenozoic Volcanism in the Mount Garibaldi and Garibaldi Lake Volcanic Fields, Garibaldi Volcanic Belt, Southwestern British Columbia - Green, Nathan (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary At least twelve Pleistocene-Holocene calc-alkaline eruptive complexes were formed in the Mount Garibaldi and Garibaldi Lake volcanic fields during the intervals 1.1-1.3 Ma, 0.4-0.7 Ma, 0.2-0.3 Ma, and 0.10 Ma to present. Mildly alkalic basalts, which resemble extensional magma types, were erupted only during the last 100,000 years. Evolution of basaltic and ésite and an-désite magmas can be explained by polybaric crystal fractionation of more mafic parental magmas. The dacitic and rhyodacitic magmas probably originated by continued fractionation of andesitic liquids accompanied by extensive assimilation of heterogeneous crustal contaminants. Erupted basalts and calc-alkaline rocks, however, cannot be related by fractionation processes.